«Calming the sands»: combating desertification on the lands of Nomadic nogais of Stavropol province in the late XIX–early XX centuries - A. T. Dzhumagulova (Nomadic Civilization: Historical Research)
The publication analyzes the peculiarities of the Russian imperial administrative experience in combating desertification in the Bazhigan and Bakylzan sand massifs of the Achikulak bailiwick of Stavropol province in the late 19th — early 20th centuries. Despite the solid historiography on the history and activities of the Forest Department as a state-legal institute of the Russian Empire, the peculiarities of the fight against sand on the lands of nomadic and transitioning to sedentary Nogai people have not become the subject of separate studies, which determines the novelty of this work. The main source base of the study was the materials extracted from the State Archive of Stavropol Krai (GASK), in particular, the materials on the strengthening of sands and afforestation in Achikulak extension, first introduced into the scientific turnover.Peculiarities of natural and geographical conditions of the Achikulak steppes and irrational use of arid zones by the Nogai people as pasture lands for large and small livestock were the main factors that caused the rapid growth of sands in the period under consideration. The beginning of the fight against sands in the Nogai steppes was laid by the government at the end of the XIX century, when the intensive spread of sands became disastrous for the local population, the bailiwick of Achikulak was threatened, and the sands began to cover the roads. In 1895–1898 in seven versts from the Achikulak bet Stavropol forestry plantation was established by the state forestry. The foresters’ activity was carried out at the expense of foreign capital of Turkmen nomadic societies living in the neighborhood with Achikulak Nogai people, thus restraining the process of sand encroachment on their nomads. For a long time Nogai people were indifferent to the process of struggle against sands. Intensive spread of sands, threat to economic life and health of nomads and neighboring peasants required state supervision, strengthening and year-round activity of foresters in the steppe. As a result of the activity of the land commission, which included the Stavropol governor, chief bailiff of nomadic peoples, surveyors of different departments, it was decided to withdraw the Bazhigan and Bakylzan sand massifs from the Achikulak bailiff and transfer them to the state supervision and care. The political events of 1917 prevented the highest government authorities from sanctioning the new delimitation of lands. Changes in the state structure, the proclamation of exclusive state socialist ownership of land and forests entailed a change in the forestry management system and the formation of a new policy in the fight against desertification in the Soviet state.